2023
DOI: 10.1021/acssuschemeng.2c06939
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Tough MXene Hydrogel Based on Interlocked Structure for Multifunctional Sensing

Abstract: Traditional hydrogel sensors containing MXenes as a conductive substrate will inevitably face the problem of excessive stacking of MXene nanosheets, which limits electron transport, thus reducing conductivity and sensitivity. Moreover, existing MXene hydrogels generally exhibit poor mechanical properties and fragility. In addition, it is necessary to prepare degradable electronic skins for reducing environmental pollution and recycling energy materialsMXene. How to find a balance between mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Typically, the degradation of hydrogel occurs due to the degradation of the polymeric backbone or cleavage of its cross-linking chemical bonds . Although physically cross-linked hydrogels have been extensively studied and considered a preferred choice, they still face challenges such as inefficient degradation rate (>3 days) and an acidic environment. To demonstrate the degradability of the PEG@PSBMA IPN hydrogel-based sensor, a piece of S 2 hydrogel was immersed in a saline solution (0.9 wt % NaCl), simulating the humoral environment. Remarkably, the S 2 hydrogel underwent almost complete degradation within 8 h at RT (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the degradation of hydrogel occurs due to the degradation of the polymeric backbone or cleavage of its cross-linking chemical bonds . Although physically cross-linked hydrogels have been extensively studied and considered a preferred choice, they still face challenges such as inefficient degradation rate (>3 days) and an acidic environment. To demonstrate the degradability of the PEG@PSBMA IPN hydrogel-based sensor, a piece of S 2 hydrogel was immersed in a saline solution (0.9 wt % NaCl), simulating the humoral environment. Remarkably, the S 2 hydrogel underwent almost complete degradation within 8 h at RT (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Several strategies have been proposed to prepare self-adhesive hydrogels, such as the introduction of catechol-containing polydopamine (PDA), 3−6 polyphenolic tannin (TA), 2,6,7 and biomimetic surface structure. 8−10 For many applications, such as underwater soft robots, 11 human implantable devices, 9,12,13 wound dressings, 10,14,15 tissue engineering, 5,8,16 and drug delivery systems, 15−18 hydrogels require dry and wet environments and wet adhesive properties. However, for viscous hydrogels, it has been shown that it is much more difficult to achieve wet adhesion than dry adhesion 3,19−21 because the water layer blocks the effective contact between the viscous hydrogel and the solid surface, leading to adhesion failure in water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Adhesion is a common interaction between two different surfaces and plays an important role in many everyday and industrial applications. Self-adhesive hydrogels are potential candidates for epidermal bioelectronic conductors. , Several strategies have been proposed to prepare self-adhesive hydrogels, such as the introduction of catechol-containing polydopamine (PDA), polyphenolic tannin (TA), ,, and biomimetic surface structure. For many applications, such as underwater soft robots, human implantable devices, ,, wound dressings, ,, tissue engineering, ,, and drug delivery systems, hydrogels require dry and wet environments and wet adhesive properties. However, for viscous hydrogels, it has been shown that it is much more difficult to achieve wet adhesion than dry adhesion , because the water layer blocks the effective contact between the viscous hydrogel and the solid surface, leading to adhesion failure in water. ,, In recent years, attempts have been made to repel the water layer by introducing hydrophobic solvents or monomers, to use highly hygroscopic components to absorb the water layer, ,, and to choose pure organic solvents as the distribution medium to exchange with the water layer to achieve underwater wet adhesion. , Although the obtained hydrogels show good wet adhesion in water, their reusability is always weak, and when the adhesion fails, they can no longer be used. ,, Another problem with the obtained hydrogels is that, unfortunately, most of the underwater adhesives lose their efficiency under oil. ,, Due to its much lower surface tension, the oil easily wets the surface, and the interfacial oil layer is more difficult to completely remove from the surface, which greatly weakens the adhesive strength between the hydrogel and the matrix under the oil, limiting their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…One possible strategy to solve this issue is to partially replace the water molecules in the hydrogel with organic reagents, such as glycerin (Gly) or ethylene glycol. 14,15 Since conductive hydrogels are generally nonrenewable or nondegradable, 16 the development of natural, low-toxic, renewable, and degradable conductive hydrogels is of utmost importance. Natural polysaccharide-based hydrogels have been recently gaining significant attention since they are biodegradable, environmentally friendly, and inexpensive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since conductive hydrogels are generally nonrenewable or nondegradable, the development of natural, low-toxic, renewable, and degradable conductive hydrogels is of utmost importance. Natural polysaccharide-based hydrogels have been recently gaining significant attention since they are biodegradable, environmentally friendly, and inexpensive .…”
Section: Introductionmentioning
confidence: 99%